Design and development of digital PID controller to control speed of permanent magnet DC motor for pcb drilling operation - Muhammad Altaf, A Jalil (2007)
Every mechanical system in this world will always be affected by the environment that prevents it from working as wanted. Normally, there are always has differences between experiment result and actual result. Drilling operation is one example of a mechanical system that is always been effected by environment during actual process. During drilling operation, the speed of the motor that rotate the cutting tool will tend to be slower from the initial speed due to the friction causes when the cutting tool makes contact with the workpiece. The reduction of speed during drilling operation will decrease the performance of the drilling operation and make it less efficient. In order to solve this problem, a controller can be use to control the speed of the motor. Digital PD controller is one of the examples. Using Digital P11), it can eliminate steady-state error and improve transient response of the system response of the motor. The theory is, when the speed of the motor become decreasing during drilling operation, the Digital PD will detect the error and will tried to eliminate it. To eliminate the error, the Digital PD will increase the voltage supplied to the motor to maintain the speed of the motor. When the speed of the motor is maintained, the performance of the drilling operation can also be maintain and become more efficient.